Estudo das fontes de financiamentos públicas dos processos ou projetos de inovação no Brasil - Scholz, Luiz Fernando de Barros (2013)
The article approaches The Study of Public Funding Sources for Innovation Processes and Projects in Brazil. This master dissertation is focused on the existing public funding sources, their effectiveness and contribution to foster R&D in Brazil. Its main objective was to present some of these existing funding sources for innovation in Brazil and their consistency with what is defined in the Oslo Manual about innovation. A secondary objective was to analyze the invested amounts and the available values to be used in innovation research and development in Brazil and to make considerations on their efficacy and efficiency. Two research techniques were used to meet those objectives. The linear regression model aimed at establishing a relation between investments and granted patents by studying the efficacy and efficiency of the investments. In this context, it was verified that the investments were effective because they have generated new patents, however, there is still space to increase their efficiency since they present a four year term to mature and a R2 of approximately 62%. This means, R2 shows that the investments explain a lot, but not all that occurs to grant the patent. The content analysis technique was used to study the consistency with the Oslo Manual. It was observed that incentive and fostering programs of R&D are adherent moderately to the Manual. There were no programs that contemplated innovation in marketing or in the operational and administrative reorganization form